2018
DOI: 10.1097/id.0000000000000747
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Radiologic Evaluation of the Dimensions of Upper Molar Alveoli

Abstract: In most cases, the alveolar sites of the upper first and second molars do not present ideal conditions for immediate implant insertion in a correct position. The primary stabilization of a standard-sized dental implant is often difficult because of the minimum apical bone available. In particular, the interradicular septum, which often represents the ideal fixture position, is rarely adequately represented. Preoperative cone-beam scan and the knowledge of anatomical measurements from the present analysis are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another important consideration when evaluating sites for an immediate implant is the buccal/lingual bone thickness. Thickness plays a significant role in bone fill after implant placement and affects bone resorption during the remodeling phase after extraction [ 23 ]. Thinner bone is affected by the interruption of blood supply during the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important consideration when evaluating sites for an immediate implant is the buccal/lingual bone thickness. Thickness plays a significant role in bone fill after implant placement and affects bone resorption during the remodeling phase after extraction [ 23 ]. Thinner bone is affected by the interruption of blood supply during the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most molars had a BBT of 1.5 mm or more [ 9 ]. However, some previous studies have reported different results [ 23 ]. Mesiodistal and buccopalatal socket measurements are critical for determining the future implant size [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maxillary molars’ interradicular septum morphometric characteristics were evaluated according to the previously described methodology [ 8 , 20 ]. Namely, in the coronal plane, we performed linear measurements (in mm, except for the angle in °) from the CBCT images as follows ( Figure 1 a,b): IRS width at the A level (2 mm from the interradicular furcation); IRS width at the B level (midpoint of IRS height); IRS width at the C level (2 mm from the IRS base); IRS width at the D level (IRS base); IRS height—h (the distance between the interradicular furcation and IRS base); The distance between IRS base and sinus floor—H; Interradicular furcation angle.…”
Section: Methodsmentioning
confidence: 99%
“…From the aspect of implantology in this specific region, numerous potential implant sites were reported in the post-extractive alveoli structure [ 3 , 4 ]. However, according to the literature data, the interradicular septum (IRS) is usually considered to be the best fixture position from the prosthetic point of view [ 5 , 6 , 7 , 8 ]. As the IRS of the maxillary molars expresses significant morphometric variability (height and width [ 9 ]), preoperative radiological analyses are highly recommended [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the interradicular bone septum represents the ideal place for immediate implant placement in the posterior region [3], in some cases, insufficient interradicular bone septum dimensions could compromise implant placement procedures [4]. In order to achieve more successful implant therapy using the interradicular bone septum as the implant place, Agostinelli and coworkers [5] reported the importance of morphological characteristics of interradicular bone septum as the criteria determining the therapy.…”
Section: Introductionmentioning
confidence: 99%